Executive dysfunction relates to salience network desegregation in behavioural variant frontotemporal dementia - Melanie A. Matyi; Hamsanandini Radhakrishnan; Christopher A. Olm; Jeffrey S. Phillips; Philip A. Cook; Emma Rhodes; James C. Gee; David J. Irwin; Corey T. McMillan; Lauren Massimo (NeuroImage: Clinical, 2025)
Background: The organization of the brain into distinct networks increases (i.e., differentiation) during development and decreases (i.e., de-differentiation) during healthy aging, changes that are associated with improvements and worsening of cognition, respectively. Given that behavioral variant frontotemporal degeneration (bvFTD) is a neurodegenerative disease associated with executive dysfunction and selective vulnerability of the salience network, we tested the hypotheses that bvFTD structural networks are de-differentiated compared to cognitively normal controls (CNC) and that network de-differentiation relates to worse executive function. Methods: In a sample of 90 patients with bvFTD and 71 age-matched CNC with diffusion MRI data we generated probabilistic tractography maps and calculated system segregation, a metric that compares within-network to between-network connectivity, to reflect the extent to which brain networks were differentiated. Patients with bvFTD also completed tests of executive function (digit span backwards, phonemic fluency, category fluency) and a control task (lexical retrieval). We assessed group differences in system segregation, reflecting network differentiation, and, within bvFTD, associations between system segregation and neuropsychological test performance. Results: Compared to CNC, patients with bvFTD exhibited lower system segregation of the salience (p < 0.001) and global brain network (p = 0.008). In bvFTD, lower salience network system segregation was associated with worse executive function (pcorrected = 0.021) but not lexical retrieval. Conclusions: Results demonstrate associations between executive dysfunction and salience network de-differentiation in patients with bvFTD. Our findings indicate that brain network de-differentiation, reflecting reduced neural capacity for specialized processing, may contribute to the emergence of executive dysfunction in bvFTD.